Combining discotic mesogens with AIE luminogens for advanced optoelectronic applications: Design, synthesis, mesomorphism, self-assembly and optical properties of tetraphenylethylene-triphenylene oligomeric conjugates - Hang Lin; Ke-Xiao Zhao; Bi-Qin Wang; Ping Hu; Ke-Qing Zhao; Bertrand Donnio (Giant)
The combination of different molecular entities with their own and specific functionalities within a single molecule enables the generation of potentially original multifunctional materials with unique properties and a broad range of applications across various fields. In this work, tetraphenylethylene (TPE) and triphenylene (TP) molecules are combined within a single oligomeric structure to yield original mesomorphic materials: TPE was chosen for its exceptional optical properties (AIE—aggregation-induced emission), while TP was included to ensure columnar self-assembly and mesomorphism. Two tetraphenylethylene-triphenylene tetrads, TPE-TP4 and TPE-ThTP4, with a crossed-shaped molecular structure, with the central TPE connecting 4 radial TP subunits, have been synthesized by the Suzuki-Miyaura coupling reaction. Both compounds exhibit high thermal stability, above 340°C. While TPE-TP4 shows only crystalline behaviour before reversibly melting into the isotropic liquid, TPE-ThTP4, which includes an additional thiophene ring bridging the central TPE and the peripheral TPs, exhibits a rectangular “multicolumnar” phase (Colrec), over a large temperature range of approximately 300°C. They also both self-assemble in fibers when mixed in various solvents to form organic gels. UV-visible absorption and fluorescence emission spectra reveal that both compounds have strong fluorescence properties in solutions and thin films, with emission wavelengths ranging between 460 and 550 nm. The absolute emission quantum yield is highly solvent-dependent, reaching a maximum of 84.5 % in cyclohexane. These tetrameric compounds also present aggregation-induced emission behaviour with a significant enhancement of the fluorescence intensity. Overall, the combination of discotic mesogens and AIE-gens within a single molecular framework holds great promises for the development of next-generation optoelectronic materials.